Revitalisasi Pembelajaran Bahasa melalui Pendekatan Sosiolinguistik untuk Penguatan Literasi dan Karakter Peserta Didik - Indramini Indramini (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Revitalizing language learning has become an urgent need in the era of globalization and digitalization, particularly in addressing the challenges of low literacy skills and weakening student character. This article aims to examine the role of a sociolinguistic approach in revitalizing language learning to strengthen students’ literacy and character in educational settings. This study employed a literature review method by analyzing various scientific sources related to sociolinguistics, language learning, literacy, and character education. The findings indicate that a sociolinguistic approach provides significant contributions to language learning because it connects language use with students’ social, cultural, and real-life communication contexts. As a result, language learning becomes more contextual, meaningful, and interactive. In addition, this approach improves students’ literacy skills, including reading, writing, and communication literacy, through the understanding of language variation, register, and the social functions of language. From the perspective of character education, sociolinguistics contributes to the development of polite language attitudes, tolerance toward linguistic diversity, and the strengthening of cultural identity. Therefore, sociolinguistic-based language learning revitalization is not only oriented toward cognitive development, but also toward students’ affective and social development. This article recommends integrating sociolinguistic approaches into curricula and language learning practices as an innovative strategy to improve the quality of language education in Indonesia.